WEB-BASED GEOGRAPHIC INFORMATION SYSTEM DESIGN, LAND MARKET PRICES ON SOCIAL MEDIA IN TSUNAMI-PRONE ZONES (CASE STUDY: PADANG CITY) - Yaseen, Egita; Yulfa, Arie (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
Transparency in land market price information is something needed by the community to prevent excessive fluctuations in land prices. Currently, there is no media that provides location-based price information. Tsunami hazard zoning also plays a role. This research formulates an information system capable of connecting the government, which officially releases land price zone values, with the local community. The research also includes information on market prices circulating on social media, in this case, Facebook Marketplace. The methodology used is SDLC with a prototype development model. In the development of WebGIS, there are two types of users: administrators who manage data and general users who are visitors or guests that only view data. This research resulted in WebGIS Land Price with six main menus: login, home, information, NJOP data, and market price data. This WebGIS makes data management easier and offers various features, including map previews and land price data searches. The conclusion of this research is that WebGIS for land prices has the potential to provide better information services to the public, with recommendations to update and enrich data in the future.